Blood pressure and diuresis in patients after kidney transplantation in the early postoperative period - Kapała, Agnieszka (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2009)
The aim of the study was to establish the range of problems, the type and quantity of interventions which nursing staff meet in the care of patients in the early postoperative period following kidney transplantation. Material and methods: The study group consisted of patients in the early period after kidney transplantation at the Transplantology and General Surgery Department of the District Hospital in Poznań. The study was conducted in the first 24 hours following the patients’ return from the operating theatre. The study was conducted between June 2006 and June 2007 and the study group consisted of 100 patients. The research method used was participant observation, and the authors used an observation chart designed by themselves. By using participant observation, the behaviour of the nurse towards the patient in the 24 hours following the transplantation was characterized. Results: Approximately 1/3 of patients in the first 24 hours following the kidney transplantation have temporary anuria for one hour and 2/3 of patients have 24-hour polyuria. In the first 24 hours after surgery, more than half of the patients (60%) required intravenous administration of diuretic drugs for forced or increased diuresis. A significant correlation was found between gender and arterial hypertension in the preoperative period in patients after kidney transplantation. Conclusion: The nursing team looking after the patient in the early period after kidney transplantation should systematically control the patient’s diuresis because of temporary anuria and/or polyuria, and in turn give the patient intravenous fluids in an optimal dose. Nursing staff should also systematically take the patient’s blood pressure, because most patients after kidney transplantation have diagnosed arterial hypertension as well as in the preoperative and postoperative period.